Low-regret control of a nonlinear parabolic problem with missing data - LAMIEN, Biéliémi; TAO, Sadou; GOUBA, Elisée (Studia Universitatis Babeș-Bolyai Mathematica, 2026)
In this paper, we study the optimal control of a nonlinear parabolic problem with missing data. Using the concepts of no-regret control, low-regret control and adapted low-regret control, we give a characterization of the con trol for ill-posed problems. More precisely, we study the control of a nonlinear parabolic problem using a regularization approach that generates incomplete information. We obtain a singular optimality system characterizing the no-regret control for the nonlinear parabolic problem. Mathematics Subject Classification (2010): 35Q93, 49J20, 93C10, 93C41. Received 24 November 2025; Accepted 18 February 2026.